2022
DOI: 10.3390/foods11233840
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Environmental Assessment of Waste-to-Energy Practices: Co-Pyrolysis of Food Waste and Discarded Meal Boxes

Abstract: The reuse of biomass waste is conducive to the recovery of resources and can solve the pollution problem caused by incineration and landfill. For this reason, the thermogravimetric analyzer (TGA) was used to study the pyrolysis of the mushroom sticks (MS) and discarded meal boxes at different heating rates (10 °C·min−1, 20 °C·min−1, 30 °C·min−1). The statistical analysis showed that the factors of pyrolysis temperature and particle size had a greater effect, while the heating rate was significant. The TGA reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…To further determine the kinetic parameters and reaction mechanism of the co-pyrolysis, six sets of values were taken for the number of reaction orders, n = 0.5, 1, 1.5, 2, 2.5, and 3 at 10 • C•min −1 to bring the experimental data into Equations ( 9) and (10) for the least-squares fitting, and the linear fitting results are shown in Table 4. In the case of PS, R 2 increases first and then decreases with the increase of n. When n = 1.5, the linear correlation coefficient is the largest (R 2 = 0.984), Ea = 78.65 kJ•mol −1 , and the linear fitting equation is Y = −9.46X + 2.68.…”
Section: Kinetic Mechanism Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further determine the kinetic parameters and reaction mechanism of the co-pyrolysis, six sets of values were taken for the number of reaction orders, n = 0.5, 1, 1.5, 2, 2.5, and 3 at 10 • C•min −1 to bring the experimental data into Equations ( 9) and (10) for the least-squares fitting, and the linear fitting results are shown in Table 4. In the case of PS, R 2 increases first and then decreases with the increase of n. When n = 1.5, the linear correlation coefficient is the largest (R 2 = 0.984), Ea = 78.65 kJ•mol −1 , and the linear fitting equation is Y = −9.46X + 2.68.…”
Section: Kinetic Mechanism Functionsmentioning
confidence: 99%
“…Currently, pyrolysis technology can be divided into liquefaction, gasification, microwave pyrolysis, catalytic pyrolysis, and co-pyrolysis [10]. Among them, some scholars have found that co-pyrolysis technology can make full use of the advantages of various raw materials to achieve hydrogen transfer under ambient pressure without high-pressure hydrogenation [11].…”
Section: Introductionmentioning
confidence: 99%
“…Common catalyst carriers include mesoporous aluminum silicates, graphene, zeolite molecular sieves (ZMS), biomass-activated carbon, and natural minerals [ 29 , 30 , 31 , 32 ]. Carbon-based carriers have attracted much attention because of their advantages of developed pore structures, large specific surface area, and low price in recent years [ 33 , 34 , 35 ]. To prepare carbon-based carriers with a developed pore structure and good dispersibility of active components have become new research focuses [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%